2022
DOI: 10.1590/s2175-97902022e19967
|View full text |Cite
|
Sign up to set email alerts
|

Intra and Extra-granular Disintegrant Properties of Modified Underutilised Red Lima Bean Starch in Paracetamol Tablet Formulation

Abstract: Red lima bean (Phaseolus lunatus Linn) Family Fabaceae, has been modified by succinylation and annealing, and used as intra-and extra-granular disintegrants at concentrations of 5 and 10 % w / w in paracetamol tablet formulation in comparison with corn starch BP. The starches were characterised using FT-IR spectroscopy, SEM, proximate analysis, physicochemical and functional properties. FT-IR spectrometry revealed characteristic peaks at 1575.53 and 1713.99 cm -1 for the succinylated starch while the annealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Fluid penetration could be through wicking; or as a result of the creation of repulsive forces, i.e. simple destruction of hydrogen bonds or the destruction of capillary cohesive forces; or a combination of both including swelling (Desai et al, 2016;Okekunle et al, 2020). Studies have shown that no single mechanism is responsible for the action of most disintegrants and tablet porosity plays a more important role than swelling as tablets having disintegrants that do not swell performed similarly to tablets having disintegrants that swell (Guyot-Hermann and Ringard, 1981;Okekunle et al, 2020).…”
Section: Drug Release Properties Of the Tabletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid penetration could be through wicking; or as a result of the creation of repulsive forces, i.e. simple destruction of hydrogen bonds or the destruction of capillary cohesive forces; or a combination of both including swelling (Desai et al, 2016;Okekunle et al, 2020). Studies have shown that no single mechanism is responsible for the action of most disintegrants and tablet porosity plays a more important role than swelling as tablets having disintegrants that do not swell performed similarly to tablets having disintegrants that swell (Guyot-Hermann and Ringard, 1981;Okekunle et al, 2020).…”
Section: Drug Release Properties Of the Tabletsmentioning
confidence: 99%
“…simple destruction of hydrogen bonds or the destruction of capillary cohesive forces; or a combination of both including swelling (Desai et al, 2016;Okekunle et al, 2020). Studies have shown that no single mechanism is responsible for the action of most disintegrants and tablet porosity plays a more important role than swelling as tablets having disintegrants that do not swell performed similarly to tablets having disintegrants that swell (Guyot-Hermann and Ringard, 1981;Okekunle et al, 2020). The disintegrant efficiency ratio (DER) generally increased as the concentration of disintegrants increased with the rank order of Sule > Giwa > Lagos.…”
Section: Drug Release Properties Of the Tabletsmentioning
confidence: 99%
“…The addition of intra and extra-granular crushing materials can increase the effectiveness of tablet disintegration through two stages, i) extra granular which breaks the tablet into granules, and ii) intra granular breaks down the granules into smaller particles. The mechanism is crushing material that experiences rapid swelling and water absorption (wicking) through the gaps between the granules and the particles that make up the granules [9]. This study aims to develop herbal FDT with the active ingredient of bay leaf ethanol extract.…”
Section: Introductionmentioning
confidence: 99%